The father heart of God - McClung, Floyd (Eastbourne, UK : Kingsway, 2006)
Contents : The wounded heart of man -- The father heart of God -- The waiting heart -- The broken heart of God -- God is a loving father -- Why God heals wounded hearts -- How God heals wounded hearts -- The Saul syndrome -- Fathers in the Lord -- Dealing with disappointment. Includes bibliographical references.
Keywords: God -- fatherhood; God -- love; Consolation